Systhesis of Carbon Based Heavy Metal Filters for Effulent Based on Rice Husk and Potting Soil - Shannon Shalen Shantasilan (2023)
This thesis was written based on research carried out to determine the absorptive capacity and the morphological structure of Agricultural Waste Bio-sorbent in terms of filtration of heavy metals. Contamination of freshwater sources by heavy metal effluents by industries has been proven to be a widely publicized issue and is currently the front running issue causing mass spread water pollution. Small to Medium industries have invested significantly due to tot he fact that they can't afford the mainstream inorganic method of heavy metal remediation due to its severely high cost. Hence the objective of this research was to study the remediation properties of the organic substances which are rice husk and potting soil. The rice husk was prepared via charring it at 500oc and then treating it with tartaric acid to modify and enhance its adsorption capabilities. 3 tests were conducted to determine the adsorptive capacity and the morphology of the activated carbon. These tests are Atomic Adsorption Spectroscopy, Scanning Electron Microscope, and BET analysis.